Critical sound in ﬂuids and mixtures - Folk, R.; Moser, G. (Condensed Matter Physics, 1999)
The behaviour of sound is explained within the dynamical renormalization
group theory. Non-asymptotic effects are due to the deviation of renormalized couplings from their ﬁxed point values. We calculate the temperature
and frequency dependence of the sound velocity and absorption near the
consolute point and the gas liquid critical point in pure ﬂuids and mixtures.
The critical non-asymptotic time scale in mixtures is different from the pure
ﬂuid case and set by an effective order parameter Onsager coefﬁcient containing the dynamical parameter related to the enhancement of the thermal conductivity. We discuss the relation to the phenomenological theory
of Ferrell and Bhattacharjee for the consolute point and compare with experiments in pure ³He, ⁴He and ³He-⁴He mixtures near the plait point. У теорії динамічної ренормалізаційної групи пропонується пояснення особливостей поведінки критичного звуку. Показано, що неасимптотичні ефекти обумовлені відхиленням ренормованих параметрів
взаємодії від їх фіксованих значень. Для ряду чистих рідин та сумішей
розраховані температурна й частотна залежності швидкості звуку і
коефіцієнта поглинання поблизу точки розшарування і критичної точки рідина-газ. Знайдено, що неасимптотичний критичний часовий
масштаб у сумішах відрізняється від того, що отримується для випадку чистих плинів, і обумовлено це зростанням ролі термопровідності. Обговорюється зв’язок з феноменологічною теорією Феррелла і Бхаттачарі для точки розшарування та проводиться порівняння
з експериментами для чистих плинів ³He і ⁴He та їх сумішей поблизу
критичної точки.